2014
DOI: 10.1186/1471-2393-14-240
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mother’s age and other related factors on neonatal survival associated with first and second birth in rural, Tanzania: evidence from Ifakara health and demographic surveillance system in rural Tanzania

Abstract: BackgroundWith a view to improve neonatal survival, data on birth outcomes are critical for planning maternal and child health care services. We present information on neonatal survival from Ifakara Health and Demographic Surveillance System (HDSS) in Tanzania, regarding the influence of mother’s age and other related factors on neonatal survival of first and second births.MethodsThe study conducted analysis using longitudinal health and demographic data collected from Ifakara HDSS in parts of Kilombero and Ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
7
21
0
Order By: Relevance
“…Earlier studies have reported a similar risk from multiple births and male foetal sex . Male sex is a risk factor for neonatal deaths and it has been suggested that male foetuses are also more vulnerable to stressors in utero . The association between neonatal deaths and birth intervals shorter than 33 months has been reported in earlier studies .…”
Section: Discussionsupporting
confidence: 52%
“…Earlier studies have reported a similar risk from multiple births and male foetal sex . Male sex is a risk factor for neonatal deaths and it has been suggested that male foetuses are also more vulnerable to stressors in utero . The association between neonatal deaths and birth intervals shorter than 33 months has been reported in earlier studies .…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies reported that maternal age and interval between consecutive births were the effective factors in the NMR (32,33). Mortality rate in the neonates whose mothers were aged 20-30 years was low, and the interval between the births more than 3 years could reduce the neonatal mortality by 40% (34).…”
Section: Discussionmentioning
confidence: 95%
“…Compared to older women, adolescents' pregnancies carry a higher risk of severe morbidities (e.g. hypertensive disorders of pregnancy) (4,5), and their children less than five years have a higher risk of death (6,7). Sub-Saharan Africa (SSA) has the second highest maternal mortality ratio (8) and the highest rate of adolescent pregnancy and childbearing globally (9).…”
Section: Introductionmentioning
confidence: 99%